Cuatro concursos de arquitectura pública - Ministerio de Obras Públicas. Chile. Dirección de Arquitectura (2008)
Concursos: Plaza Sotomayor, Vaparaíso; Museo de la Memoria, Santiago; Edificio CorreosChile, Santiago; Centro Cultural Gabriela Mistral, Santiago.